VD_FINDINFO HC / 2012 / 441 vom 28. Juni 2012 - VD Tribunal cantonal (2012)
DROIT DE GARDE, OBLIGATION D'ENTRETIEN, CONVENTION{COMPÉTENCE DES AUTORITÉS EN MATIÈRE DE PROTECTION DES MINEURS} | 176 CC, 308 al. 1 CPC, 48 LDIP, 85 al. 1 LDIP, 2 CLaH 96, 3 CLaH 96, 5 CLaH 96